Self-standing and shape-memorable UV-curing epoxy polymers for three-dimensional (3D) continuous-filament printing. Issue 12 (7th March 2018) - Sun, H.; Kim, Y.; Kim, Y. C.; Park, I. K.; Suhr, J.; Byun, D.; Choi, H. R.; Kuk, K.; Baek, O. H.; Jung, Y. K.; Choi, H. J.; Kim, K. J.; et al.
Abstract : Hydrogen-bond networks with adjacent molecules were formed to provide a developed material, which has self-standing solid-like characteristics enabling its implementation in 3D continuous-filament printing. Abstract : In the development of three-dimensional printable materials for high-speed and high-resolution printing, UV-curing polymers can guarantee fast and precise printing of high performance load-bearing structures, but the injected drops of the monomers tend to spread over the substrates due to their low viscosity. In this study, we imposed the self-standing and shape-memorable capability of an epoxy acrylate (EA) monomer to ensure continuous filamentary 3D printing while maintaining its low viscosity nature. Using octadecanamide (ODA) with EA, strong hydrogen-bond networks (−N−H⋯OC−, −N−CO⋯H–O–, –N–H⋯N–) were additionally achieved in the material system and the developed material distinctively exhibited rheological duality at different processing stages: a low-viscosity liquid-like behavior (viscosity of ∼50 Pa) while passing through the nozzle and a self-standing solid-like behavior (static yield stress of ∼364 Pa) right after being printed. This reversible liquid-to-solid transitional capability was quantified by viscoelastic complex moduli provided a dynamic yield stress ( τ y, G ) of 210 Pa corresponding to the upright stacking up to ∼3.2 cm (3 wt% of ODA). The time ( t y, G ) required for conformational rearrangement was evaluated to be as fast as ∼10 −2 s. After UV curing, the 3D printed layers exhibited no air pockets or weld lines at the stacked interfaces, which could guarantee excellent mechanical performance and structural integrity.